2022
DOI: 10.1002/pssa.202100772
|View full text |Cite
|
Sign up to set email alerts
|

Hyperdoped Crystalline Silicon for Infrared Photodetectors by Pulsed Laser Melting: A Review

Abstract: Infrared photodetectors based on crystalline silicon have attracted much attention due to their low cost and good compatibility with complementary metal–oxide–semiconductor (CMOS) technology in ultra‐largescale integrated circuits (ULSI). However, silicon shows no response to infrared light with a wavelength of over 1100 nm corresponding to its bandgap of 1.12 eV. Pulsed laser melting and rapid solidification are effective ways to hyperdope high concentrations of deep‐level impurities into silicon, and therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…[ 28 ] Notably, in our previous study, it has been shown that Si:Zn photodetector with conventional annealing at 700 °C for 30 min as post‐treatment exhibits a responsivity of 0.68 mAW −1 at 1550 nm, −1 V bias, which is not so satisfactory. [ 8 ] Therefore, exploring a more efficient annealing process may be an effective approach to enhance the performance of Si:Zn photodetectors. RTA is a method of annealing that involves direct irradiation of the sample surface by a radiation source, rapidly heating the sample to the target temperature within a very short period of time.…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ] Notably, in our previous study, it has been shown that Si:Zn photodetector with conventional annealing at 700 °C for 30 min as post‐treatment exhibits a responsivity of 0.68 mAW −1 at 1550 nm, −1 V bias, which is not so satisfactory. [ 8 ] Therefore, exploring a more efficient annealing process may be an effective approach to enhance the performance of Si:Zn photodetectors. RTA is a method of annealing that involves direct irradiation of the sample surface by a radiation source, rapidly heating the sample to the target temperature within a very short period of time.…”
Section: Resultsmentioning
confidence: 99%
“…In general, either planar or roughsurfaced hyperdoped materials can be achieved and the process is referred to as optical hyperdoping [10,56,57]. The dopant incorporation dynamics and light-trapping properties are reviewed in [58], and we highlight several important concepts in order to compare this doping technique to others.…”
Section: Thin-film or Gas Phase Dopant Precursormentioning
confidence: 99%
“…Several photodetectors have been developed using this approach [10,53,75,78,138], and reviewed in [58,139]. In general, these devices showed EQE higher than 100% for above bandgap light, indicating a photoconductive gain is taking place.…”
Section: Devices With Different Hyperdoping Techniquesmentioning
confidence: 99%
“…However, the high manufacturing costs of compound semiconductor infrared detectors limit their integration with silicon-based chips. Therefore, infrared photodetectors based on crystalline silicon have gained attention due to their low cost and compatibility with complementary metal oxide semiconductor (CMOS) technology in ultra-large-scale integrated circuits (ULSI) [5,6]. Unfortunately, the bandgap of silicon at 1.12 eV limits its absorption of infrared light above 1100 nm [7,8], which has motivated the development of processes compatible with the silicon-based semiconductor industry to expand silicon's infrared light absorption [9].…”
Section: Introductionmentioning
confidence: 99%